Enantioselective synthesis of (−)-chloramphenicol via silver-catalysed asymmetric isocyanoacetate aldol reaction. Issue 1 (29th October 2015) - Franchino, Allegra; Jakubec, Pavol; Dixon, Darren J.
Abstract : A concise synthesis of (−)-chloramphenicol, based on the catalytic asymmetric aldol reaction between 4-nitrobenzaldehyde and benzhydryl isocyanoacetate, is reported. Abstract : The highly enantio- and diastereoselective aldol reaction of isocyanoacetates catalysed by Ag2 O and cinchona-derived amino phosphines applied to the synthesis of (−)- and (+)-chloramphenicol is described. The concise synthesis showcases the utility of this catalytic asymmetric methodology for the preparation of bioactive compounds possessing α-amino-β-hydroxy motifs.